4-Hydroxybenzoic acid for multiple system atrophy?. (May 2018) - Distelmaier, Felix
Abstract: Increasing evidence supports a link between multiple system atrophy and coenzyme Q10 (CoQ10 ) biosynthesis. However, so far this knowledge was not translated into tangible benefits for affected patients. Poor bioavailability of oral CoQ10 might constitute a major problem. Current research suggests that 4-hydroxybenzoic acid might constitute an interesting alternative treatment option.